Constructed Landscape - Michael Hughes (Oz, 2006)
The Joy House, one of seven buildings operated by the nonprofit Providence Network, provides up to two years of temporary shelter and counseling for women and children affected by domestic violence. The client’s programmatic requirements were initially limited to pragmatic code compliance issues.